Ciencia y turismo: construyendo territorialidad. Representaciones sociales y prensa escrita - Cohen, Carolina; Morgavi, Mariana; Vereda, Marisol (Facultad de Humanidades Universidad Nacional del Comahue, 2022)
The construction of territoriality implies the participation of diverse agents who take part in society by contributing with different approaches, knowledge and ways of appropriating space. Written press takes a stance acting as a communicator of social, cultural, political and economic processes, being able to become an agent of change in the appropriation and delimitation of space. Ushuaia and Punta Arenas are positioned as two of the five gateways to Antarctica, due to their location and functionality, playing a fundamental role by having the ability to provide different services necessary for governmental and non-governmental activities to be developed in Antarctica. From this perspective, the aim of this contribution is to analyze the place that science and tourism occupy as strategy in the construction of territoriality for these two gateway cities to Antarctica, Ushuaia and Punta Arenas. A qualitative methodology based on the content analysis of documents from mass media corresponding to press genre (national and provincial) from January 1 to December 31, 2019 was implemented. The results reflect the topics of interest of each city, showing coincidences in some cases and differences in others, depending on the priorities assigned by each territory. The work presents the different relationships between the written press and the geographical space, depending on the social groups involved and their interests, as well as according to the scalar level. It also shows that there are various aspects that contribute to the construction of territoriality. La construcción de territorialidad implica la participación de diversos agentes que intervienen aportando miradas, saberes y formas de apropiar el espacio. La prensa escrita se posiciona como comunicadora de los procesos sociales, culturales, políticos y económicos que acontecen pudiendo actuar como agente de cambio en la apropiación y delimitación espacial. Ushuaia y Punta Arenas se posicionan como dos de las cinco puertas de entrada a la Antártida, debido a su ...